Coping experiences of young adults diagnosed with a chronic illness: a qualitative systematic review protocol. Issue 12 (18th December 2021) - Wilson, Beth; Weeks, Lori; Morris, Patricia; Innocente, Sarah; Rothfus, Melissa
ABSTRACT: Objective: The objective of this review is to gain insight about the experience of emerging adults who are coping with a chronic illness diagnosis. Introduction: Receiving a chronic illness diagnosis is filled with challenges and changes to a person's life. Coping is not an easy or linear process, and is particularly complex for emerging adults. The emerging adult stage is important to consider, as this is a stage characterized by identity exploration, transition to adulthood, and future planning. A chronic illness diagnosis interrupts these processes and affects the coping process in emerging adults. Inclusion criteria: The population included will be persons between 18 and 25 years of age living in the community. Sources will focus on the experience of being diagnosed with a chronic illness, including its impacts on the individual's life. Methods: This qualitative review will be conducted following JBI qualitative review methodology. An initial search was conducted in order to identify relevant articles on the topic. Databases to be searched include CINAHL, PubMed, PsycINFO, and Nursing and Allied Health Database. A gray literature search will also be conducted. There will be no date or language limits on the search. The titles and abstracts will be screened by two independent reviewers, followed by an assessment of the full-text articles. Any disagreements will be resolved through discussion or in consultation with a third reviewer. Critical appraisal of included articles and data extraction will be conducted independently by two reviewers. Meta-aggregation of the articles will be completed and textually pooled in tabular format. Where that is not possible, results will be presented in a narrative format. Systematic review registration number: PROSPERO CRD42021224772